The Influence of Competence and Work Discipline on the Performance of Sewing Department Employees at PT Adis Dimension Footwear, Tangerang Regency - Syawalisa, Dinda; Cahyono, Yoyok; Putra, Awang Darmawan (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The purpose of this study was to determine how much influence work competence and work discipline have on the performance of employees in the Sewing NCVS 1.13 division at PT Adis Dimension Footwear, Tangerang Regency. This study uses a quantitative method. The population in this study were all employees in the Sewing NCVS 1.13 division at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 63 respondents. The results of this study indicate that work competence and work discipline have an effect on employee performance. This means that the better the level of competence and work discipline of employees at PT Adis Dimension Footwear, the better the employee performance will be. The results of the discussion show that there is a good influence, both partially and simultaneously, between work competence and work discipline on employee performance at PT Adis Dimension Footwear. This explains that both variables have succeeded in improving employee performance with an Adjusted R Square of 75.8%.